Review on the monograph by doctor Beata Glinkowska "Internationalization of Polish and Ukrainian enterprises" - Liashenko, V. (Економічний вісник Донбасу, 2018)
Review on the monograph: Beata Anna Glinkowska, Internacjonalizacja polskich i ukraińskich przedsiębiorstw (978-8-3814-2134-8), Wydawnictwo Uniwersytetu Łódzkiego, Łódź 2018. 454 stron.